Impaired retinal vasodilator response to acetylcholine in a rat model of NMDA-induced retinal degeneration - Asami Mori; Masayuki Hanada; Kenji Sakamoto; Tsutomu Nakahara; Kunio Ishii (Elsevier, 2015)
Previous studies have shown that degeneration of retinal capillaries occurs following N-methyl-d-aspartate (NMDA)-induced retinal neurotoxicity, but it is unclear whether vasodilatory mechanisms are altered in retinal blood vessels. The purpose of the present study was to determine whether retinal vasodilator responses are affected in a rat model of NMDA-induced retinal damage. At 14 days after a single intravitreal injection of NMDA (200 nmol), retinal vasodilator responses were assessed by measuring the diameter of retinal arterioles in fundus images. Acetylcholine-induced vasodilation of retinal arterioles was significantly reduced in NMDA-treated retinas, whereas retinal vasodilatory effects of the nitric oxide (NO) donor NOR3, the β2-adrenoceptor agonist salbutamol, and the β3-adrenoceptor agonist CL316243 were unaltered. The vasodilator response to acetylcholine observed under the combined blockade of NO synthase and cyclooxygenase with NG-nitro-l-arginine methyl ester (30 mg/kg, i.v.) plus indomethacin (5 mg/kg, i.v.), possibly an endothelium-derived hyperpolarizing factor-mediated response, was also reduced. These results suggest that endothelium-dependent vasodilatory mechanisms in retinal blood vessels are impaired in the rat model of NMDA-induced retinal degeneration. Glutamate-induced neurotoxicity is implicated in several retinal diseases; therefore, abnormal retinal circulation would contribute to the progression of the diseases.